Confirmation of the power gain for solar photovoltaic systems in alpine areas and across scales - Frischholz, Y.; Schilt, U.; Sharma, V.; Kahl, A.; Strebel, S.; Anderegg, D.; Rohrer, J.; Lehning, M. (Frontiers in Energy Research, 2024)
High Alpine regions show a great potential for solar photovoltaics electricity production in winter due to the reflective properties of snow and the larger number of sun hours compared to lower urban and peri-urban regions. In countries with a pronounced deficit in domestic electricity production such as Switzerland, utility-scale projects of Alpine-PV power plants are now flourishing. The harsh environmental conditions and the complexity of the high-Alpine topography however challenge the conventional design practices. In this context, the main question the article addresses is the representation of test-scale measurement in the performances of Alpine-PV, utility-scale power plants. This article focuses on the comparison between long term tests and the first Alpine-PV utility-scale power plant in Switzerland. The results show that the main performance indicators such as the Alpine-to-Midlands final yield ratio or the winter fraction, do scale. However, absolute final yield values are consistently lower at the utility scale. The paper discusses the possible impacts of the complex Alpine topography as constraint for the design of the larger extent of utility-scale power plants as well as the influence of scale on the snow induced losses.